Analisis Teknik Budidaya dan Organisme Pengganggu Tanaman (OPT) Terhadap Produksi Padi di Desa Bumi Restu Kabupaten Halmahera Timur - Risna Mangamis; Suratman Sudjud; Suryati Tjokrodiningrat; Sri Soenarsih; Sartika Syafi; Abd. Rahmat Mandea (Jurnal Pertanian Khairun, 2025)
Rice (Oryza sativa L.) is a major staple crop that plays a strategic role in ensuring national food security. This study aims to analyze the relationship between cultivation techniques and the intensity of pest and disease (organism pest of plants/OPT) attacks on rice yield in Bumi Restu Village, East Halmahera Regency. The research was conducted at three locations using a field survey method and a quantitative approach. Data were collected through direct observation and structured interviews with 30 farmers, then analyzed using Pearson correlation and multiple linear regression with SPSS 25. The results revealed that the highest pest attack intensity occurred during the generative phase, categorized as mild to moderate. Regression analysis indicated that the rice planting system significantly influenced yield. The average yield of harvested dry grain (GKP) was 6.08 tons/ha at Location I, 5.0 tons/ha at Location II, and 6.4 tons/ha at Location III. Therefore, the adoption of the jajar legowo planting system and integrated pest management (IPM) is recommended to sustainably enhance rice productivity.